CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE TAX BEHAVIOR: THE DUAL ROLE OF CSR IN EXPLAINING LEVERAGE AND TAX AGGRESSIVENESS - Parso; Lily Nabilah (Jurnal Ekonomi dan Manajemen, 2026)
This study examines the role of Corporate Social Responsibility (CSR) as both a mediating and moderating variable in the relationship between leverage and tax aggressiveness. The research focuses on food and beverage companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The study employs a quantitative approach using secondary data obtained from annual reports and financial statements. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that CSR does not have a significant effect on tax aggressiveness. In addition, leverage is not found to significantly influence CSR or tax aggressiveness. The moderation analysis also shows that CSR does not significantly moderate the relationship between leverage and tax aggressiveness. Furthermore, mediation testing confirms that CSR does not mediate the relationship between leverage and tax aggressiveness. These findings suggest that CSR disclosure does not necessarily reflect corporate tax responsibility in the Indonesian food and beverage sector.